Educação protestante em Goiás: entre modernidade e tradição nos institutos Samuel Graham – Jataí e Granbery – Pires do Rio (1942-1963) - Muniz, Tamiris Alves (2020)
This research is linked to the Graduate Program in Education - UFU, line of research: History and Historiography of Education, and has as its object the history of Protestant education in the state of Goiás based on the study of two confessional schools installed in the state in the early 1940s, one Presbyterian, the Samuel Graham Institute (1942), created in the city of Jataí, in the southwestern region of the state, and another Methodist, the Granbery Institute (1943), created in Pires do Rio, in the southeastern region. The choice of these institutions is justified because they are part of the same historical state context and are the first Protestant schools created in Goiás, related to a specific religious denomination of Protestantism and at the same time they are distinct, but with similar purposes, which allows the analysis of how these two institutions were situated in time and space and were crossed, each in its own way, by the religiosity and the context that forged them. Thus, the objective of the research is to know the founding elements of these two institutes, their subjects, their materiality, their purposes, their representations and formalized practices, and to establish relationships between them, inferring to what extent these institutes, announced as an expression of modernity, of the American education, presented such aspects and whether they were innovative or not, and what they meant for education in Goiás, a state of Catholic majority. The time frame includes the period 1942-1963, marked by the creation of the Samuel Graham Institute and the closure of the Granbery Institute. The research is based on the theoretical field of the History of Education, especially in the History of School Institutions, influenced by the assumptions of Cultural History, emphasizing the concept of School Culture and using the comparison as a methodological unit, in order to identify the characteristics of these institutions, the problems that involved them and their development characteristics and thus understand their historical meaning. It is a research of documental and bibliographical nature. The bibliographic research was based on authors of expression in the theoretical-methodological debate, such as Magalhães (1998; 2004), Chartier (1990; 2002), Viñao Frago (1998; 1995) and Ramalho (1976). The sources are mainly school documents produced by the two institutions, such as: internal regulations, minutes of school meetings, visiting books, enrollment forms and books, curricular programs, statistical bulletins, prospectuses and photographs. The results corroborate the importance of the religious element in the creation of these institutions, which in addition to being their purpose, was decisive for their permanence. Despite the discourse of modernity used by these institutions as a differential element, there were some elements of an innovative character that came closer to the North American and Protestant educational model inaugurated in the country, but they were mostly based on school infrastructure, while a set of traditional aspects stood out and characterized the educational experience of these institutions. However, the experience of these two institutes proved to be important for education in Goiás, occupying part of the educational void of the period, mainly in high school, and shedding light on aspects of educational renewal in vogue and the Protestant presence in the Goiás educational field, the relationship between religion and education, tradition and modernity.